2021
DOI: 10.5812/ijpbs.108390
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methylphenidate (MPH) and Combined Methylphenidate with Crocus sativus (Saffron) in the Treatment of Children and Adolescents with ADHD: A Randomized, Double-blind, Parallel-Group, Clinical Trial

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is characterized by behavioral and neurodevelopmental problems. It is estimated that 3 - 7% of children and adolescents suffer from this problem. Apart from synthetic drugs, other effective types of medication like herbal medicines are of great importance. Objectives: This study aimed to evaluate the effectiveness of methylphenidate (MPH) and its combination with Crocus sativus (saffron) in the treatment of children suffering from ADHD. Methods: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
(52 reference statements)
0
17
1
1
Order By: Relevance
“…This is in keeping with the recent literature. Several recent clinical trials examined the efficacy and safety of saffron extract to treat ADHD symptoms [ 20 , 21 , 22 ]. All three of them found that saffron is an effective and safe treatment for ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is in keeping with the recent literature. Several recent clinical trials examined the efficacy and safety of saffron extract to treat ADHD symptoms [ 20 , 21 , 22 ]. All three of them found that saffron is an effective and safe treatment for ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Baziar et al [ 20 ] showed a similar effect for saffron and methylphenidate in children. Khaksarian et al [ 21 ] showed that combining saffron with methylphenidate was more effective for treating ADHD symptoms in children than methylphenidate alone. Pazoki et al [ 22 ] found a similar boosting effect in adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations